The Study of Al-Mashun Historic Mosque in Medan City from the Historical and Aesthetic Appraisals - Hidayat, Wahyu; Ganie, Tunggul H (Talenta Publisher, 2020)
The protection of tangible cultural heritage as an effort to preserve the nation's patrimony is an endeavor to strengthen the nation's treasure and identity. A set of such protection is no longer a subsidiary act but is a fundamental part of urban planning. The historic or ancient building is a tangible cultural heritage that is unmovable. A building is categorized as historic if it has essential value for prehistoric, present, scientific, and artistic functions with at least 55 years of age. Natural and human-made heritage can be in the form of buildings for commercial, cultural, educational, and religious purposes, family houses, industrial areas or government buildings, parks, bridges, old cities, historic neighborhoods, or traditional residential groups. This study aims to identify the Al-Mashun Mosque as a historic building. Several features are compiled such as name, location, owner, date of construction, original and current use, category, condition, description, history, significance/value, photo, source, founder, and the recommendation for rehabilitation/ revitalization/ conservation /preservation efforts in the concerned area or other matters considered to be necessary. This study is expected to assist efforts to preserve the Al-Mashun Mosque as a historic building in Medan City by optimizing its potential through conservation, preservation, revitalization/adaptation, rehabilitation/restoration, and reconstruction measures. Hopefully, Medan City is expected to have identity and characteristics in formulating the beauty of the city and promoting cultural tourism, while still involving the private sector and community participation.